Idioms in the Lyrics of Indonesian Dangdut Songs - Kelabora, Noni Welina; Rutumalessy, Merlyn (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze idioms in the lyrics of the dangdut songs "Sms," "Sambalado," "Keong Racun," "Belah Duren," "Paling Suka 69," and "Jatuh Bangun." This research is qualitative, utilizing a natural setting to understand occurrences through diverse methodologies. The lyrics of this dangdut song incorporate idioms that include body parts, sensory terms, color names, natural items, animal names, plant names or parts, and numerous lexical categories.